Sustainable Practices in Urban Horticulture: A Review of Green Infrastructure - C.D.N. Sinha (International Journal of Trends in Horticulture, 2025)
Urbanization is expanding at an unprecedented rate across the globe, which brings about significant challenges, including environmental degradation, climate change, and the rapid loss of biodiversity. As the population in cities grows and urban areas become increasingly congested, the role of urban horticulture is becoming vital in improving the livability and sustainability of these environments. Urban horticulture plays an important role in enhancing both the ecological and social fabric of cities, offering solutions to many of the environmental issues faced by urban populations. This review delves into sustainable practices in urban horticulture, focusing particularly on green infrastructure as a key strategy. Utilizing natural processes and systems, like soil, water, and plants, to solve environmental issues is known as "green infrastructure. By incorporating nature-based solutions like green roofs, vertical gardens, and urban farms into the urban landscape, cities can mitigate a wide range of environmental concerns, including poor air quality, flooding, and the urban heat island effect. Additionally, these systems enhance biodiversity, offering spaces for both flora and fauna within the city. Green infrastructure also improves the quality of life for urban residents by providing aesthetic value, promoting recreational spaces, and fostering community engagement through urban farming and gardening initiatives. This paper explores various green infrastructure techniques utilized in urban horticulture, outlining their associated benefits, such as environmental resilience, food security, and social cohesion. It also discusses the challenges these practices face, including space constraints, high initial costs, and the need for proper maintenance. Finally, the review offers insights into the future potential of these sustainable practices in transforming cities into more resilient, healthy, and sustainable environments for future generations.
Keywords: Environmental sustainability; Green infrastructure; climate resilience; sustainable practices; urban agriculture; urban horticulture